E-059 Guiding Sclerotherapy for Deep Lying Lesions using Advanced Angiographic Imaging Applications and MR-Fusion. (26th July 2014) - Aagaard-Kienitz, B; Elijovich, L; Schafer, S; Royalty, K; Field, A
Abstract : Background: Deep head and neck lesions are challenging to treat using conventional guidance, such as ultrasound (US) and fluoroscopy. High impedance structures prevent the use of US, while fluoroscopy lacks resolution of the targeted lesion. Recently developed tools allow the fusion of 3D MR images with low-dose DynaCT images of the patient and enable different guidance methods for successful deep lesion treatment. Two approaches were investigated; overlaying the lesion in MR images on the live fluoroscopy images and path planning and target delineation on MR images with subsequent path and target overlay on live fluoroscopy images. Methods/materials: Patients underwent general anaesthesia followed by a low-dose DynaCT scan ( 1/20 dose of Head CT). T2 weighted MR images were imported and fused with the low-dose DynaCT image. For overlay on fluoroscopy, the lesion was identified and segmented. Needle advancement into the overlaid lesion was then performed (Figure 1a ). When using path planning, an unobstructed path was constructed to the target avoiding bony or critical structures (Figure 1c ). The path was overlaid on live fluoroscopy and the needle advanced. Prior to injection, a confirming low-dose DynaCT was acquired to assess needle placement and, if required, corrections were performed. Sclerosing agent was then injected. A final low-dose DynaCT, fused to MR, and the distribution of the agent with respect to the lesion was evaluated (Figure 1b, d ). Findings: Using a combination of MR/ultralow dose DynaCT fusion and low dose fluoroscopic imaging single pass needle placement into deep sub-osseous cystic facial lesions or deep ocular lesions was performed in multiple patients. Benefit of fusion imaging with microcystic lesions was also found. Post-treatment, repeat fusion after sclerotherapy was performed and demonstrated accurate intra-lesion deposition without extravazation. For microcystic lesions, fusion improved conspicuity of the overall target lesion and confirmed sclerotherapy confined to target territory. Focus on low-dose DynaCT and sclerotherapy specific fluoroscopy settings reduced radiation dose compared to standard protocols while providing procedure specific information. Conclusion: Use of limited MR fused to ultra-low dose DynaCT displayed with low dose fluoroscopy provides improved lesion visualization during sclerotherapy treatment and may improve treatment accuracy and clinical outcomes. Disclosures: B. Aagaard-Kienitz: None. L. Elijovich: 2; C; consultant for Microvention, Stryker, and J and J Codman. S. Schafer: None. K. Royalty: 6; C; employee, Siemens Medical Solutions, USA, Inc., Hoffman Estates, IL. A. Field: 2; C; Consultant for Asterias Biotherapeutics, Inc.